2007
DOI: 10.1007/s10725-007-9241-8
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous auxin affects ascorbate metabolism in roots of tomato seedlings

Abstract: Ascorbate levels and redox states, as well as the activities of the enzymes of ascorbate metabolism, were analyzed in roots of tomato seedlings during the culture on a medium supplemented with auxin and compared to the control cultured on an auxin-free medium. Biochemical parameters were determined separately in the distal part of the root where the inhibitory effect of auxin on root elongation growth is observed and in the proximal half on the organ which reacts to auxin treatment with increased lateral root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Ascorbate derives its role from its sensitivity to ROS and from the fact that its oxidation affects the redox balance of other metabolites, such as glutathione which themselves are involved in the perception of the cellular redox unbalance (Apel and Hirt 2004). Our results are supported by the data obtained by Tyburski et al (2008) indicating that the presence of exogenous auxin in the culture induced an increase in ascorbate level in the roots of tomato seedlings.…”
Section: Discussionsupporting
confidence: 84%
“…Ascorbate derives its role from its sensitivity to ROS and from the fact that its oxidation affects the redox balance of other metabolites, such as glutathione which themselves are involved in the perception of the cellular redox unbalance (Apel and Hirt 2004). Our results are supported by the data obtained by Tyburski et al (2008) indicating that the presence of exogenous auxin in the culture induced an increase in ascorbate level in the roots of tomato seedlings.…”
Section: Discussionsupporting
confidence: 84%
“…In our previous study we reported on the fact that auxin stimulates the activity of ascorbate peroxidase (APX). In contrast to CAT, auxin induced an increase in the activity of this enzyme in the proximal part of the root (Tyburski et al 2008).…”
Section: Discussionmentioning
confidence: 70%
“…These data suggest that the process of root elongation is dependent on optimal GSH level in the growing part of the organ and that the mechanism of inhibition of root growth by auxin may possibly involve the accumulation of supraoptimal GSH levels. Other redox factors such as ROS (Joo et al 2001;Liszkay et al 2004) and ascorbate (Tyburski et al 2008) were also found to be implicated in the inhibition of root elongation by exogenous auxin. Fig.…”
Section: The Effect Of Gsh Bso and Iaa On Root Regeneration And Growthmentioning
confidence: 97%